Developmental Trajectories Leading to Hostility Toward Women: A Structural Equation Modeling Study - Deli, Caroline (Violence against women, 2025)
Hostility toward women is frequently examined as a risk factor for violence against women, but research on its antecedents is sparse. The aim of this study was to explore the developmental and psychological antecedents associated with hostility toward women in a Canadian sample of sexual aggressors of women. Drawing on Malamuth’s confluence model of sexual aggression, we developed a multifactorial model of hostility toward women, using structural equation modeling. The results indicate the presence of three trajectories, all starting from childhood victimization and leading to hostility toward women, involving antisocial characteristics, emotional negativity, anxiety, and depression.